Wysokość udziałów jednostek samorządu terytorialnego we wpływach z podatków dochodowych - Pest, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the influence of the percentage of shares and tax structure elements on the level of local government units income from shares. In the first part of the article the evolution of legal regulations of the percentages of shares in subsequent acts regulating the issues of the local government units income is presented. In the second part, the impact of the subject, the object, the tax base, tax deductions, exemptions and tax rates on the level of shares is presented.
Keywords: local government units; income taxes; level of shares